2019
DOI: 10.3389/fpls.2019.00436
|View full text |Cite
|
Sign up to set email alerts
|

A Major Root Architecture QTL Responding to Water Limitation in Durum Wheat

Abstract: The optimal root system architecture (RSA) of a crop is context dependent and critical for efficient resource capture in the soil. Narrow root growth angle promoting deeper root growth is often associated with improved access to water and nutrients in deep soils during terminal drought. RSA, therefore is a drought-adaptive trait that could minimize yield losses in regions with limited rainfall. Here, GWAS for seminal root angle (SRA) identified seven marker-trait associations clustered on chromosome 6A, repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 99 publications
5
73
1
Order By: Relevance
“…For example, root spread angle is an additional feature whose variation can influence how crops cope with water-limited conditions and/or other environmental constraints, such as high pH, toxic ions, or low nutrient availability [45,46]. The root angular spread at an early growth stage can be used to predict the partitioning of root biomass in the soil profile at the adult plant stage [5,27,28], a feature relevant for water use efficiency in wheat [21,47]. Therefore, artificial systems are efficient at revealing phenotypic (and presumably genetic) variability, but its implications on agronomic performance must be validated later under field conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, root spread angle is an additional feature whose variation can influence how crops cope with water-limited conditions and/or other environmental constraints, such as high pH, toxic ions, or low nutrient availability [45,46]. The root angular spread at an early growth stage can be used to predict the partitioning of root biomass in the soil profile at the adult plant stage [5,27,28], a feature relevant for water use efficiency in wheat [21,47]. Therefore, artificial systems are efficient at revealing phenotypic (and presumably genetic) variability, but its implications on agronomic performance must be validated later under field conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies have found useful associations with traits in adult plants of wheat species [23][24][25][26]. For instance, the seminal root angle was correlated with nodal root angle [5,27], and with grain yield under drought conditions [28]. The seminal root number was correlated with thousand kernel weight (TKW) under stress, while the primary root length at the seedling stage was correlated with TKW under wetter conditions [25].…”
Section: Introductionmentioning
confidence: 99%
“…A panel comprising 168 genotypes was evaluated in this study. The panel included 151 durum lines from the NAM population developed at the University of Queensland [39]. The NAM population was generated by crossing eight lines from ICARDA's durum breeding program in Morocco with two Australian cultivars.…”
Section: Plant Materialsmentioning
confidence: 99%
“…To investigate the relationship between root biomass and yield under CR conditions, a subset of the panel (40 genotypes) was selected according to the haplotype at the major QTL for root angle qSRA-6A (i.e., hap1 = narrow, n = 20; and hap2 = wide, n = 20) [39]. The 40 genotypes were evaluated for root biomass using the method reported by Voss-Fels et al [57] with slight modifications.…”
Section: Phenotyping Root Biomass Under Controlled Conditionsmentioning
confidence: 99%
See 1 more Smart Citation